Functional Interactions of Tau Phosphorylation Sites That Mediate Toxicity and Deficient Learning in Drosophila melanogaster - Keramidis, Iason; Vourkou, Ergina; Papanikolopoulou, Katerina; Skoulakis, Efthimios M. C. (Frontiers in Molecular Neuroscience, 2020)
Hyperphosphorylated Tau protein is the main component of the neurofibrillary tangles, characterizing degenerating neurons in Alzheimer’s disease and other Tauopathies. Expression of human Tau protein in Drosophila CNS results in increased toxicity, premature mortality and learning and memory deficits. Herein we use novel transgenic lines to investigate the contribution of specific phosphorylation sites previously implicated in Tau toxicity. These three different sites, Ser238, Thr245 and Ser262 were tested either by blocking their phosphorylation, by Ser/Thr to Ala substitution, or pseudophosphorylation, by changing Ser/Thr to Glu. We validate the hypothesis that phosphorylation at Ser262 is necessary for Tau-dependent learning deficits and a “facilitatory gatekeeper” to Ser238 occupation, which is linked to Tau toxicity. Importantly we reveal that phosphorylation at Thr245 acts as a “suppressive gatekeeper”, preventing phosphorylation of many sites including Ser262 and consequently of Ser238. Therefore, we elucidate novel interactions among phosphosites central to Tau mediated neuronal dysfunction and toxicity, likely driven by phosphorylation-dependent conformational plasticity.